ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY FOR STUDYING DSSC ELECTROLYTES - Naimjonov Arslonbek Maxammadjon o`g`li (TADQIQOTLAR, 2025)
Abstract. Dye-sensitized solar cells (DSSCs) rely critically on the electrolyte to regenerate the dye, transport redox species, and sustain charge-transfer at the counter electrode while limiting recombination at the photoanode interface. Electrochemical impedance spectroscopy (EIS) is one of the most informative nondestructive methods for separating bulk electrolyte transport from interfacial kinetics and diffusioncontrolled processes across a broad frequency window. This review consolidates the theoretical basis of impedance spectroscopy in forms directly usable for DSSC electrolyte research, with emphasis on Nyquist/Bode interpretation, constant-phase behavior, diffusion impedance, and the relationship between fitted parameters and physically meaningful electrolyte properties such as ionic conductivity, effective permittivity, diffusion coefficient, mobility, and charge-carrier concentration. We provide a rigorous and practical workflow for designing EIS experiments in symmetric "dummy" cells and complete DSSCs under dark and illumination, highlight pitfalls related to non-stationarity and model non-uniqueness, and describe validation using Kramers-Kronig consistency tests. Representative electrolyte formulations- including iodide/triiodide liquid electrolyte and gel polymer electrolytes based on PAN/EC/PC with iodide salts and ionic-liquid iodides, as well as polymer blends such as PVP/PMMA-are discussed to illustrate how composition and morphology impact impedance signatures. The review closes with reporting recommendations aimed at improving reproducibility and comparability across studies, enabling EIS-guided electrolyte optimization toward higher efficiency and improved stability DSSCs [1,2].